Non‐prescription medicines may contribute to non‐adherence to prescription medicines in people living with chronic health conditions. Issue 6 (4th March 2020) - Anoopkumar‐Dukie, Shailendra; Mey, Amary; Hall, Susan; Bernaitis, Nijole; Davey, Andrew K.; Plummer, David
Abstract: Background: Non‐adherence to prescribed medicines is linked to adverse health outcomes in people living with chronic health conditions (CHCs). Multiple factors are known to contribute to non‐adherence to medicines including polypharmacy, demographic features and disease and health systems. Both non‐prescription and prescription medicines contribute to polypharmacy; however, there is limited data on the influence of non‐prescription medicines to non‐adherence. Aim: Therefore, the aim of the study was to investigate the influence of non‐prescription medicines to non‐adherence in an Australian population. Methods: Data from the 2016 National Survey of a random sample of Australian adult residents were utilised in this study to investigate factors associated with non‐adherence. Descriptive statistics, χ 2, regression and generalised linear models were used to assess the relationships between variables of interest. Narrative response and comments were used to provide further insight. Results: This study recruited 1217 participants to explore factors associated with non‐adherence to medicines. Weak but statistically significant correlations were identified showing the number of CHCs, patient's age, number of prescription medicines, number of non‐prescription medicines and total number of medicines associated with non‐adherence. Discussion: The findings suggest that people living with CHCs and taking multiple medicines, including non‐prescription medicines, are likely to be non‐adherent to prescription medicines. This study shows the possible involvement of non‐prescription medicines in contributing to non‐adherence in an Australian population and suggests that future studies with a broader demographic are warranted.